Effects of telephone-based motivational interviewing in lifestyle modification program on reducing metabolic risks in middle-aged and older women with metabolic syndrome: A randomized controlled trial. (August 2016) - Lin, Chia-Huei; Chiang, Shang-Lin; Heitkemper, Margaret McLean; Hung, Yi-Jen; Lee, Meei-Shyuan; Tzeng, Wen-Chii; Chiang, Li-Chi
Abstract: Background: Lifestyle modification is often difficult for middle-aged and older women living in the community who are at high risk of physical inactivity and metabolic syndrome. Objectives: To examine the effects of telephone-based motivational interviewing in a 12-week lifestyle modification program on physical activity, MetS, metabolic risks (fasting plasma glucose, blood pressure, triglyceride, high-density lipoprotein, and central obesity), and the number of metabolic risks in community-living middle-aged and older women diagnosed with metabolic syndrome. Research design and method: A randomized controlled trial was conducted. Recruited were 328 middle-aged and older women from a community health center in Taiwan. Eligible women medically diagnosed with metabolic syndrome ( n = 115) were randomly assigned to one of three groups: The experimental group received an individualized telephone delivered lifestyle modification program that included motivational interviewing delivered by an experienced nurse. The brief group received a single brief lifestyle modification counseling session with a brochure. The usual care group received standard care. Physical activity was assessed with the International Physical Activity Questionnaire and metabolic risks were determined by serum markers and anthropometric measures at pre- and post-intervention. One hundred women completed the study and an intention-to-treat analysis was performed. Generalized estimating equations were used to examine the intervention effects. Results: Women in the experimental group increased physical activity from 1609 to 1892 MET-min/week ( β = 846, p = .01), reduced the percentage of diagnosed with metabolic syndrome to 81.6% ( β = −0.17, p = .003), and decreased the number of metabolic risks from 4.0 to 3.6 ( β = −0.50, p < .001), compared to the usual care group (4.4–4.6). There was not a reduction in the percentage of diagnosed with metabolic syndrome in the brief group, but they had fewer metabolic risks after 12 weeks (mean = 4.0 vs. 4.6, β = −0.2, p = .02) compared to the usual care group. Conclusions: Motivational interviewing as a component of an individualized physical activity and lifestyle modification program has positive benefit in reducing metabolic risks in middle-aged and older women.